Analysis of personal and work-related factors contributing to construction industry accidents in Peru - Salazar Tenorio, Juan Francisco (2023)
The purpose of this research is to examine the relationship between individual and occupational risk factors and accidents at road construction sites in Lima, Peru. The research was conducted using a correlational design, analyzing the causes of accidents through safety inspection reports and independent accident investigations. The study population included all employees who suffered lost-time accidents during their workday. Associations between variables were determined using descriptive statistics, inferential statistics, and comparative tables. The results suggest that personal and occupational factors contribute to accidents at road construction sites in Lima, Peru. After the root causes of accidents were identified and addressed, the accident rate decreased significantly in 2017 and 2018. Supervision was found to be the primary means of accident prevention, while leadership is essential to motivate workers to adhere to established standards of conduct.